The role of voiding cystourethrography in asymptomatic unilateral isolated ureteropelvic junction obstruction: A retrospective study. Issue 2 (April 2017) - ElSheemy, Mohammed S.; Ghoneima, Waleed; Abdelwahhab, Mohammad; Aboulela, Waseem; Daw, Kareem; Shouman, Ahmed M.; Shoukry, Ahmed I.; El Ghoneimy, Mohamed; Morsi, Hany A.; Badawy, Hesham
Summary: Introduction: The presence of concomitant vesicoureteric reflux (VUR) and ureteropelvic junction obstruction (UPJO) is uncommon. Nevertheless, the reported VUR coexisting with asymptomatic unilateral isolated hydronephrosis (AUIH) requiring pyeloplasty for correction of UPJO was of low grade and mostly resolved during conservative follow-up. Therefore, VCUG may be not indicated in these children except if voiding symptoms, urinary tract infection (UTI), dilated ureters, or bladder and ureteric abnormalities are suspected. Objectives: The aim was to evaluate the need for VCUG in infants <1 year old with AUIH for whom a dismembered pyeloplasty was indicated for correction of UPJO. Methods: Ninety-six children <1 year old with pyeloplasty carried out from January 2012 to March 2014 were retrospectively included. Children with voiding symptoms or dilated ureter, duplex system, fused kidneys, bilateral dilatation, or any bladder abnormality on ultrasound were excluded. Anderson–Hynes pyeloplasty was performed through a flank incision. Preoperative VCUG was analyzed in relation to outcome and any UTI during follow-up. The Student t test, Mann–Whitney U test, or Fisher exact test were used to compare variables. Results: Five children had concomitant VUR with UPJO. Most of the children were circumcised during the first postnatal week. The remaining few children were circumcised at the time of pyeloplasty. Side, grade of detected VUR, and complications (18.75%) (postoperative or during follow-up) are presented in theTable . Outcomes in children with and without VUR were not different. Dismembered pyeloplasty was successful in children with VUR and with no complications except for non-febrile UTI in one child only. Ureters were still not dilated at the last follow-up. Discussion: The required imaging in infants with AUIH is still a subject of debate. As we expected, there was a low incidence of associated VUR in the present study. They were of low grade without any complications during follow-up and without affecting the outcome. The present study has its limitations, including the retrospective nature and short follow-up. However, as at least 2 years of follow-up were documented without any harm or ureteric dilation, VUR will mostly resolve. The present study is strengthened by inclusion of infants only. Conclusions: Our data suggest that VCUG is not indicated in infants with AUIH requiring pyeloplasty for correction of UPJO. VCUG will not affect the treatment decision, operative outcome, or postoperative complications. VCUG may be indicated in case of suspected voiding symptoms, UTI, dilated ureters, or bladder and ureteric abnormalities. Table Detected VUR and outcome in all patients.   Number of patients (%) VUR in VCUG 5/96 (5.2%)  Ipsilateral 4 (4.16%)  Contralateral 1 (1.04%) Grade of detected VUR  Grade 1 5/5 (100%) Complications (postoperative and during follow-up): 18/96 (18.75%)  Non-febrile UTI 4/96 (4.16%)  Febrile UTI 1/96 (1.04%)  Leakage 7/96 (7.3%)  Wound infection 1/96 (1.04%)  Obstruction 5/96 (5.2%) Redo-pyeloplasty 3/96 (3.12%) VUR = vesicoureteric reflux; VCUG = voiding cystourethrography.